Efektifitas Media Video Tutorial Meningkatkan Keterampilan Seni Grafis (Sablon Cukil) pada Anak Disabilitas Intelektual Ringan - Zalda, Nanda; Zulmiyetri, Zulmiyetri; Tsaputra, Antoni; Yuliana, Syari (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to determine the effectiveness of video tutorial media in improving linocut screen-printing skills among eighth-grade students with mild intellectual disabilities at SLB Negeri 1 Ranah Pesisir. The research employed a Single Subject Research (SSR) A–B design, consisting of a baseline phase without intervention and an intervention phase using video tutorials. The participant was one student who experienced difficulties in carving image patterns. Data were collected through direct observation using a skill assessment sheet and analyzed visually by examining changes in level, trend, and stability. The findings show a significant improvement in the student's linocut skills, increasing from 56% during the baseline phase to 100% at the end of the intervention. These results indicate that video tutorial media is effective in enhancing vocational skills, particularly linocut screen-printing, and serves as an innovative, concrete, and engaging learning strategy for students with mild intellectual disabilities.